Dietary metabolic energy/lysine ratios improve the yolk color and Hastelloy unit without affecting the egg performance of brown laying hens - Du, Jiagang; Zhuang, Rufei; Zhang, Yuanju; Wang, Yan; Liu, Yunguo; Zhang, Qianqian; Zhang, Jianying (Frontiers in Animal Science, 2025)
This experiment evaluated the impact of varying ratios of dietary metabolic energy: lysine (ME: Lys) in the diet on egg production, egg quality, and feed intake of laying hens. A total of 432 Hy-line brown laying hens, aged 55 wk, were reared over a period of 11 weeks. Hens were individually assigned to a basal standard diet with a ME to Lys ratio of 275:64 kcal/mg, along with five additional ratio types: 270:74 kcal/mg, 275:74 kcal/mg, 280:74 kcal/mg, 285:74 kcal/mg, and 290:74 kcal/mg. Feed and fecal digestibility were determined and egg quality were assayed on wk 1, 5, 9 and 11. The results indicated that an ME/Lys ratio of 285:74 kcal/mg improved yolk color pigment during weeks 9 and 11. Additionally, a ratio of 290:74 kcal/mg contributed to higher Hastelloy unit measurements during weeks 5, 9, and 11. In summary, while different ME/Lys ratios had no impact on overall egg production, both the 285:74 and 290:74 kcal/mg ratios demonstrated positive effects on deeper yolk color pigment and higher Hastelloy unit values.